2021
DOI: 10.1002/smll.202105958
|View full text |Cite
|
Sign up to set email alerts
|

Application and Development of Shape Memory Micro/Nano Patterns

Abstract: Shape memory polymers (SMPs) are a class of smart materials that change shape when stimulated by environmental stimuli. Different from the shape memory effect at the macro level, the introduction of micro‐patterning technology into SMPs strengthens the exploration of the shape memory effect at the micro/nano level. The emergence of shape memory micro/nano patterns provides a new direction for the future development of smart polymers, and their applications in the fields of biomedicine/textile/micro‐optics/adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 153 publications
0
19
0
Order By: Relevance
“…On the other hand, researchers adjust surface microgeometry to switch the wettability of the surface to obtain new functions. Some efforts have been expended on shape memory polymers by virtue of their good shape memory effect, attempting to realize the goal of dynamic wettability switching. Nevertheless, almost all previous studies are focused on tuning the microstructure induced by the cooperative effect of pressure and thermal stimulation. Interestingly, some applications such as no-loss transfer of a given droplet require more sensitive in situ switching of surface wettability. For this reason, elastic substrates are widely applied to adjust the surface microstructure dynamically via mechanical strain. ,, Goel et al reported an anisotropic buckled surface with dual-scale roughness, on which the droplet rolls more easily in the direction parallel to the wrinkles .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, researchers adjust surface microgeometry to switch the wettability of the surface to obtain new functions. Some efforts have been expended on shape memory polymers by virtue of their good shape memory effect, attempting to realize the goal of dynamic wettability switching. Nevertheless, almost all previous studies are focused on tuning the microstructure induced by the cooperative effect of pressure and thermal stimulation. Interestingly, some applications such as no-loss transfer of a given droplet require more sensitive in situ switching of surface wettability. For this reason, elastic substrates are widely applied to adjust the surface microstructure dynamically via mechanical strain. ,, Goel et al reported an anisotropic buckled surface with dual-scale roughness, on which the droplet rolls more easily in the direction parallel to the wrinkles .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Shape memory polymers (SMPs) with pattern-memorizing surfaces obtained by combining SMPs and the micro-pattern technology are a class of novel smart materials with multi-functions, whose unique capability enables significant applications ranging from tunable optical devices, flexible electronic devices, smart textiles, adjustable wettability to switchable medical devices. [7][8][9][10][11][12][13][14][15][16] Compared with the single macroscopic scale deformation of traditional SMPs, the introduction of a micro-structure not only expands the exploration of shape memory behavior at the micro-nano level, but also endows superior scientific significance for smart materials in the following: [17][18][19] first, the pattern-memorizing surface can precisely regulate the surface function of SMPs regionally; second, smart multi-functional materials can be achieved by the synergetic dynamic change of macroscopic shape and micro-pattern, such as dynamic wettability, intelligent adhesion and adjustable friction; third, microstructures on the SMP surface can tune the programming of macro-shapes to add active functions, such as bending, twisting or contraction direction, deformation degree and directed movement. Therefore, the development of SMPs with a pattern memory surface is of great significance to promote the progress of intelligent multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows examples of thermo-responsive shape-memory surfaces with micron-scale surface patterns. The current body of work shows that thermo-responsive surfaces are limited to a switch and recovery cycle 39 of a single permanent surface pattern, also referred to as a dual shape-memory effect. The examples in Table 1 point to two research gaps that limit the programing of multiple shape memories with micron-scale surface patterns: (i) the use of homopolymers limits the material system to a single thermal transition point and (ii) the types of fabrication methods used are limited to a single processing window.…”
Section: Introductionmentioning
confidence: 99%